The interaction between local employment development and corporate social responsibility : Final report. Contract reference n°VC/2007/0559 - Austrian Institute for SME Research, Vienna; Mandl, Irene (Vienna, 2009)
"Recent years have been characterised by an enhanced involvement of local actors in designing and implementing employment policies in the European Union. Thereby, a partnership or multi-stakeholder approach is promoted, i.e. the co-operation among governments, employers’ and employees’ organisations, the civil society (e.g. Non- Governmental Organisations (NGOs), Non-Profit Organisations (NPOs), the church, social enterprises) and private businesses. Companies may be triggered to participate in policy-oriented local activities on the basis of their Corporate Social Responsibility (CSR) activities which can be observed to increasingly spread across the European business community."